Passages from the French and Italian note-books of Nathaniel Hawthorne. - Hawthorne, Nathaniel, 1804-1864. (Tufts University. Tisch Library., 2016)
Wayside edition.; 1 online resource (574 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.